Does Emotion before a Chemotherapy Course Break a Heart? Cardiogenic Shock Complicating Takotsubo Cardiomyopathy - K, Taamallah; Y, Arous; A, Haggui; N, Hajlaoui; W, Fehri; F, Msaddek (Cardiology and Cardiovascular Medicine, 2022)
Introduction: Takotsubo cardiomyopathy is characterized by a broad spectrum of clinical presentations. Despite its reversibility, it is associated with severe adverse in-hospital events. Recent studies have identified a high incidence of TTC in cancer patients. Case Report: We report the case of a 59-year-old-man with TTC occurring just before injecting of chemotherapy drug complicated by cardiogenic shock and acute heart failure. Under medical treatment, a complete recovery of cardiac contractility was noted within three days. chemotherapy regimen has been stopped and then alleviated from RCHOP to the RCVD. No recurrence of cardiac symptoms was noted during the follow-up period. Left ventricle ejection fraction, BNP, and troponin levels were maintained normal. Conclusion: Takotsubo cardiomyopathy can occur in cancer patients leading to interruption of chemotherapy because of left ventricular dysfunction, which may adversely affect the oncologic outcome because of interruption of cancer treatment. We report this case to remind clinicians that TTC should be considered in the differential diagnosis of chest pain in cancer patients who present with ECG findings characteristic of acute coronary syndrome. We hope to facilitate prompt diagnosis for an early intervention that allows rapid recovery of myocardial function, and resume cancer therapy early and may help lower mortality.